Dampak dan Perlindungan Hukum Pelecehan Seksual Terhadap Perempuan di Tempat Umum (Cat Calling) - M. Ahlul Fikri (CV WAHANA PUBLIKASI, 2023)
Sexual harassment is unwanted sexual behavior or attention that disrupts a person’s life. Sexual harassment has many impacts, especially on the mental state of victims of sexual harassment. The psychological impacts experienced by victims of sexual harassment can be depression, panic, loss of motivation and many others. Not only the psychological impacts that will be experienced by victims of sexual harassment, there are also social impacts where the victim will be judged badly by the community around him. The purpose of writing this journal is to find out what impacts will be experienced by victims of sexual harassment and to find out what protections are obtained by victims of sexual harassment. This journal writing uses the normative juridical method. Sexual harassment has become an issue that often occurs in society, especially cat calling which is considered commonplace but is actually a violation of moral values ​​that makes the victim uncomfortable and experiences a verbal impact in the form of taunting whistles to the victim of catcalling.